Evaluating the effectiveness of different beta-adrenoceptor blockers in heart failure patients. (1st March 2017) - Lin, Tien-Yu; Chen, Chung-Yu; Huang, Yaw-Bin
Abstract: Background: According to guidelines and pivotal trials, β-blockers are associated with better survival in patients with heart failure (HF). However, the superiority of any β-blockers is still unclear. Methods: This retrospective cohort study was conducted using the National Health Insurance Research Database in Taiwan to evaluate the effectiveness of β-blockers and compare the clinical outcomes of different β-blockers in patients with HF. We enrolled patients diagnosed with HF between 2005 and 2012. We then stratified the β-blockers according to the starting dose: lower in group 1 and higher in group 2. A time-dependent Cox proportional hazards regression model was applied to evaluate the effectiveness of the β-blockers. Results: A total of 14, 875 patients with HF were identified during the study period. After propensity-score matching, 5688 patients were included in both the β-blocker user and nonuser groups. We found that group 2 carvedilol and group 2 bisoprolol significantly reduced the risk of death and hospitalization for HF, whereas metoprolol did not. Compared with group 2 carvedilol, survival was not significantly different for group 2 bisoprolol (adjusted hazard ratio = 1.18, 95% confidence interval = 0.88–1.58). Conclusion: From results, carvedilol and bisoprolol were associated with better outcomes, with no difference between these two β-blockers in patients with HF in Taiwan.